Arterial Hypertension and Unusual Ascending Aortic Dilatation in a Neonate With Acute Kidney Injury: Mechanistic Computer Modeling - Altamirano-Diaz, Luis; Kassay, Andrea D.; Serajelahi, Baran; McIntyre, Christopher W.; Filler, Guido; Kharche, Sanjay R. (Frontiers in Physiology, 2019)
Background: Neonatal asphyxia caused kidney injury and severe hypertension in a newborn. An unusually dilatated ascending aorta developed. Dialysis and hypertensive treatment led to partial recovery of the ascending aortic diameters. It was hypothesized that the aortic dilatation may be associated with peripheral resistance and cardiovascular changes. Mathematical modelling was used to better understand the underlying causes of the hypertension, and the associated aortic dilatation. Methods: The patient’s arterial blood pressure showed hypertension. Echocardiographic exams showed ascending aorta dilatation during hypertension, which partially normalized upon antihypertensive treatment. To explore underlying mechanisms of the aortic dilatation and hypertension, an existing lumped parameter hemodynamics model was deployed. Simulations were designed to permit examination of causal mechanisms. The hypertension inducing effects of vascular resistances, stiffnesses, and cardiac hypertrophy on blood flow and pressure were simulated. Sensitivity analysis was used to stratify treatment options. Results: In agreement with our clinical diagnosis, the model showed that an increase of the systemic small vessel resistance is a prime cause of hypertension. Further, aortic stiffening, which may also cause hypertension, was found to be secondary. Ascending aortic pressure and flow increased in the simultaneous presence of left ventricle hypertrophy and augmented small vessel resistance, which indicate a plausible condition required for ascending aorta dilatation. In contrast, increased arterial stiffness lowered the aortic blood flow and pressure. Sensitivity analysis showed that the treatment of the small vessel resistance is more relevant than the treatment of large vessel stiffness or cardiac hypertrophy. The model’s pulmonary circulation was also affected by arterial hypertension causing factors. Conclusions and discussion: Peripheral small vessel resistance is an important factor in arterial hypertension, and may also be a key clinical therapeutic target. Left ventricle hypertrophy may be simultaneously ameliorated upon pharmacological treatment of small vessels. Treatment of arterial stiffness appears to provide significant benefit but may be secondary to treatment of small vessels, which represent microvasculature. The quantitative grading of pathophysiological mechanisms provided by the modelling may contribute to treatment recommendations. Model limitations are the absence of mechanisms such as dynamic mechano-structural function and autoregulation, as well as data suitable to permit model identification.